A bridge too far? An academic-national security practitioner dialogue on research collaboration across the divide. Issue 1 (2nd January 2021) - Grossman, Michele; Davis, Natalie
ABSTRACT: In a well-known article, Marc Sageman (2014, The stagnation in terrorism research. Terrorism and Political Violence, 26 (4)) foregrounds what he calls the 'unbridgeable gaps' between national security agencies and academics on the question of accessing and analysing the empirical data upon which innovative terrorism research depends. Yet while the divide between academic research and national security policy and practice can be pronounced, it is also mediated by the existence of common territory. This includes ideas about what constitutes 'the public good', despite bringing varied institutional, personal and philosophical approaches to how that good is understood and enacted. At their best, where these collaborations are embraced and nurtured, they can become unparalleled opportunities for expanded learning, constructive provocation and informed debate, bringing different forms of expertise to bear on understanding and reducing the risks and impacts of terrorism. At their worst, they can be minefields of compromised independence, ethical and reputational wounds, censorship, exploitation, and hollow research and policy agendas. We take up these issues through an edited collaborative dialogue between an academic and a national security practitioner, drawing on both the scholarly literature and our own experience as collaborators to explore the benefits, conflicts and risks of academic-national security collaboration.